Shift and Share Technique for Forecasting Regional and Sectoral Growth-A Review and an application for India March 1981 - Planning Commission (Planning Commission, 1981)
This working paper reviews and applies the Shift and Share (S&S) technique to analyze and forecast regional and sectoral economic growth in India within the framework of the UNDP Transport Policy Planning Project. By decomposing national growth into national, industry mix, and regional competitive effects, the study evaluates state-level performance using historical sectoral data and projects growth patterns for the Sixth Five-Year Plan period. The analysis reveals significant inter-state and inter-sectoral disparities, with faster growth in infrastructure-related and industrial sectors compared to agriculture, and evidence of gradual regional convergence. Complementary sectoral share analysis further illustrates shifts in state dominance and sector resilience over time. Despite limitations in forecasting service-sector growth and highly disaggregated data, the paper demonstrates the practical value of the S&S technique for regional planning, policy formulation, and strategies aimed at achieving balanced economic development in India.
Government of India Planning Commission (UNDP Transport Policy Planning Project)
Government of India Planning Commission (UNDP Transport Policy Planning Project)
Keywords: Shift And Share Technique; Regional And Sectoral Growth; Sixth Five Year Plan; State Domestic Product; National Growth Effect; Industry Mix Effect; Differential Shift; Regional Disparities; Sectoral Share Analysis; Economic Planning In India